Mobile service delivery in response to the opioid epidemic in Philadelphia - Rebecca E. Stewart; Hanna P. Christian; Nicholas C. Cardamone; Catherine Abrams; Caroline Drob; David S. Mandell; David Metzger; Margaret Lowenstein (Addiction Science & Clinical Practice, 2023)
Abstract Background The harms of opioid use disorder (OUD) and HIV infection disproportionately impact marginalized populations, especially people experiencing homelessness and people who inject drugs (PWID). Mobile OUD service delivery models are emerging to increase access and reduce barriers to OUD care. While there is growing interest in these models, there is limited research about the services they provide, how they operate, and what barriers they face. We characterize the capacity, barriers, and sustainment of mobile OUD care services in a large city with a high incidence of OUD and HIV. Methods From May to August 2022, we conducted semi-structured interviews with leadership from all seven mobile OUD care units (MOCU) providing a medication for OUD or other substance use disorder services in Philadelphia. We surveyed leaders about their unit’s services, staffing, operating location, funding sources, and linkages to care. Leaders were asked to describe their clinical approach, treatment process, and the barriers and facilitators to their operations. Interview recordings were coded using rapid qualitative analysis. Results MOCUs are run by small, multidisciplinary teams, typically composed of a clinician, one or two case managers, and a peer recovery specialist or outreach worker. MOCUs provide a range of services, including medications for OUD, wound care, medical services, case management, and screening for infectious diseases. No units provide methadone, but all units provide naloxone, six write prescriptions for buprenorphine, and one unit dispenses buprenorphine. The most frequently reported barriers include practical challenges of working on a MOCU (e.g. lack of space, safety), lack of community support, and patients with substantial medical and psychosocial needs. Interviewees reported concerns about funding and specifically as it relates to providing their staff with adequate pay. The most frequently reported facilitators include positive relationships with the community, collaboration with other entities (e.g. local nonprofits, the police department, universities), and having non-clinical staff (e.g. outreach workers, peer recovery specialists) on the unit. Conclusions MOCUs provide life-saving services and engage marginalized individuals with OUD. These findings highlight the challenges and complexities of caring for PWID and demonstrate a need to strengthen collaborations between MOCU providers and the treatment system. Policymakers should consider programmatic funding for permanent mobile OUD care services.